2020
DOI: 10.1158/1078-0432.ccr-19-2390
|View full text |Cite
|
Sign up to set email alerts
|

Coaltered Ras/B-raf and TP53 Is Associated with Extremes of Survivorship and Distinct Patterns of Metastasis in Patients with Metastatic Colorectal Cancer

Abstract: We aimed to investigate genomic correlates underlying extremes of survivorship in metastatic colorectal cancer and their applicability in informing survival in distinct subsets of patients with metastatic colorectal cancer. Experimental Design: We examined differences in oncogenic somatic alterations between metastatic colorectal cancer cohorts demonstrating extremes of survivorship following complete metastasectomy: 2-year (n ¼ 17) and 10-year (n ¼ 18) survivors. Relevant genomic findings, and their associati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 50 publications
2
52
2
Order By: Relevance
“…When a random forest model was applied, the metastatic sites were predicted by the conditions of several genes frequently found in CRC. Datta et al [28] reported that metastatic CRC tumors harboring co-occurring RAS/BRAF and TP53 alterations were significantly more likely to involve extrahepatic metastatic sites compared with tumors that were RAS/BRAF-altered or TP53-altered only. This analysis considered the synergistic effects of the three genes, and the results for key genes were similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…When a random forest model was applied, the metastatic sites were predicted by the conditions of several genes frequently found in CRC. Datta et al [28] reported that metastatic CRC tumors harboring co-occurring RAS/BRAF and TP53 alterations were significantly more likely to involve extrahepatic metastatic sites compared with tumors that were RAS/BRAF-altered or TP53-altered only. This analysis considered the synergistic effects of the three genes, and the results for key genes were similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Datta and coworkers explored a large group of 935 patients with metastatic CRC and showed that co-alteration of oncogenic TP53 with either KRAS , NRAS , or BRAF mutations was associated with significantly worse survival compared to alterations in either gene group alone [ 59 ]. Interestingly, RAS/BRAF-TP53 co-mutated CRCs were associated with worse survival in patients with liver and lung, but not with peritoneal surface metastases Moreover, co-altered BRAF/RAS-TP53 were significantly associated with the development of extra-hepatic metastatic sites [ 59 ].…”
Section: Liver Metastasesmentioning
confidence: 99%
“…Datta and coworkers explored a large group of 935 patients with metastatic CRC and showed that co-alteration of oncogenic TP53 with either KRAS , NRAS , or BRAF mutations was associated with significantly worse survival compared to alterations in either gene group alone [ 59 ]. Interestingly, RAS/BRAF-TP53 co-mutated CRCs were associated with worse survival in patients with liver and lung, but not with peritoneal surface metastases Moreover, co-altered BRAF/RAS-TP53 were significantly associated with the development of extra-hepatic metastatic sites [ 59 ]. Similar conclusions were reached by Kawaguchi et al who analyzed the possible relationship between somatic gene mutation profile and outcome in 507 metastatic CRC patients who underwent CLM resection: BRAF , RAS , TP53 , and SMAD4 mutations were significantly associated with overall survival, coexisting mutations in RAS , TP53 , and SMAD4 were associated with negative outcome (reduced OS and RFS) than coexisting mutations in any two of these genes and mutations in one or more of these genes [ 60 ].…”
Section: Liver Metastasesmentioning
confidence: 99%
“…In primary CRC, the prognostic value of RAS has been suggested to be limited to MSS cancers and to depend on the consensus molecular subtypes (34). In patients with resectable CRLM, the prognostic value may depend on co-occurring TP53 mutations (12,13) or TP53/SMAD4 mutations (14).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in RAS have consistently been associated with a poor prognosis among patients with resectable colorectal liver metastases (CRLM) (7)(8)(9), and it has been suggested that surgical treatment is less bene cial in patients with RAS mutations (10). However, the prognostic effect size is modest (11) and it was recently proposed that the effect is limited to tumors with co-occurring TP53 mutations (12,13), or co-occurring TP53 and SMAD4 mutations (14). BRAF V600E mutations have a stronger prognostic effect size, but the prognostic value is limited by the low prevalence of this marker among patients with resectable CRLM (15).…”
Section: Introductionmentioning
confidence: 99%